Poligami dalam Hermeneutika Feminis Amina Wadud - Anam, Haikal Fadhil (Sunan Kalijaga State Islamic University & The Asia Foundation, 2020)
Artikel ini menelaah poligami dalam perspektif hermeneutika feminisme ala Amina Wadud. Buku Qur’an and Woman Rereading the Sacred Text from a Woman’s Perspective adalah landasan dasar dalam perwakilan pandangan Amina Wadud pada tiga pembahasan penting dalam pemikiran pada konsep pembebasan, konsep patriarkhi, dan klasifikasi makna feminis. Penulisan ini membedah hakikat pemikiran Amina Wadud pada hak perempuan dan kebebasan poligami dengan syarat. Islam adalah agama kebebasan dalam menata muamalat dalam pola pernikahan yang rahmatan lilalamin.[The article talks about polygamy in Amina Wadud's hermeneutic feminism theory. The base paper, the Qur'an and Woman Rereading the Sacred Text from a Woman's Perspective, is an essential root in Amina Wadud's thought view. Three meaningful discussions are in Amina Wadud's thoughts on freedom concepts in human rights, patriarchal concepts inhabit rule and classification of feminist meaning in the text Qur'an. This paper examines Amina Wadud's thoughts on women's rights and the polygamy perspective with the rule. Islam is a peaceful religion in engaging relationships in a pattern of marriage.]